Effect of bacterial products on neutrophil migration in vitro. Issue 4 (April 1990) - Ras, G; Wilson, R; Todd, H; Taylor, G; Cole, P
Abstract : Chronic bronchial inflammation is associated with migration of large numbers of granulocytes into the bronchial tree. A study was designed to find out whether products of bacteria commonly isolated in chronic bronchial infection stimulate neutrophil migration in vitro. Neutrophils from healthy donors were studied by a modified Boyden chamber technique. Bacterial culture filtrates stimulated neutrophil migration over a wide dilution range and the chemotactic activity was heat stable. Culture filtrates derived from Pseudomonas aeruginosa, Streptococcus pneumoniae, and Haemophilus influenzae were significantly chemokinetic and directionally chemotactic, whereas filtrates from Staphylococcus aureus were only chemotactic. Gel filtration of S aureus and P aeruginosa culture filtrates yielded high, medium, and low molecular weight fractions showing chemotactic activity. S pneumoniae and H influenzae yielded fractions with only low molecular weight chemotactic activity. Neutrophil chemotactic responses, occurring in response to all bacterial species tested, appear to represent a defence mechanism by the host. Chemoattractant activity may, however, contribute to bronchial damage mediated by products released from continuously attracted, activated neutrophils.